Violence as the Manifestation of Simulacra in Salman Rushdie’s Novel “Shame” - Radavičiūtė, Jūratė (Respectus Philologicus, 2015)
The article analyses Salman Rushdie's novel Shame from the perspective of portraying two female characters Bilquis Hyder and her daughter Naveed and how the violence underlying the instability of the images they construct manifests itself. The research is carried out within the theoretical framework of postmodernism with the view to the concept of the postmodern sign elaborated by Jean Baudrillard and Jacques Derrida. The postmodern sign is characterised by the loss of a reference to reality which is masked by the abundance of supplements for reality. The vulnerability of such a sign is revealed through the process of crisis the sign is subjected to, because it uncovers the void underlying the simulacrum of the sign. The portrayal of Hyder women reveals the concept of the simulacrum from the point of view of its reliance on thingness for existence. The indeterminacy of the simulacrum is revealed through the repeated occurrence of the images of the wind and childbirth, which signify the threat of violence underlying the simulacrum.
Keywords: Rushdie; Shame; Simulacra; Postmodernism; Sign